Developing the PAOCS Scale (Perceptions and Attitude toward Oral Communication in Science) for Postsecondary Science Students - Simon Langlois; Caroline Cormier (ADMEE-Canada, 2021)
The ability to communicate orally is important in science, but few tools assess students' perceptions and attitude toward scientific oral communication in scientific programs. This research developed the Perceptions and attitude towards oral communication in science (PAOCS) questionnaire for postsecondary students with the theoretical model associated. A sample of 1,295 Quebec college students in a natural sciences program participated in this research, responding to the three versions of the questionnaire during the stages of its development. Principal component analyses (PCA) followed by a confirmatory factor analysis (CFA) made it possible to identify five factors for the PAOCS questionnaire: pleasure, anxiety, perceived relevance, and two aspects of self-efficacy (SEOCS), namely the Norms & Content SEOCS, which relates to the effectiveness in expressing oneself orally, and the Showmanship SEOCS , which describes rather how to be dynamic and capture the attention of the audience. The overall evaluation of the PAOCS shows that this questionnaire has good psychometric qualities and that the components obtained during the validation process support the theoretical model.